The Correlation of Motivation With Student Learning Outcomes Fourth Grade Elementary School: Hubungan Motivasi Dengan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Faizah, Jahrotul; Wati , Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the relationship between motivation and learning outcomes of fourth grade students at SDN Juwet Kenongo Porong Sidoarjo. This research uses quantitative research. The method used is ex post facto. The design used in this study is poduct moment correlation. The instrument used in the study was a questionnaire. The samples in this study were all fourth grade students of SDN Juwet Kenongo Porong Sidoarjo using saturated samples. The data analysis technique used in this research is validity, reliability, and hypothesis testing. The results showed that motivation has a relationship with student learning outcomes.